SINERGI LEMBAGA KEBUDAYAAN, MELEBURKAN KONFLIK DAN TUMPANG TINDIHNYA FUNGSI LEMBAGA - Hartatik, nfn (Balai Arkeologi Kalimantan Selatan, 2007)
Multiple cultural institutions, either belong to government or non government often cause some overlapping function and obligations. How to prevent such overlapping ? This paper discuss case studies available in Kalimantan . Some solutions are offered i.e: proportional distribution of cultural institution, coordination among different cultural institutions, and managerial and cultural archiving systems improvement.